Strong‐Coupled Cobalt Borate Nanosheets/Graphene Hybrid as Electrocatalyst for Water Oxidation Under Both Alkaline and Neutral Conditions. (12th January 2016) - Chen, Pengzuo; Xu, Kun; Zhou, Tianpei; Tong, Yun; Wu, Junchi; Cheng, Han; Lu, Xiuli; Ding, Hui; Wu, Changzheng; Xie, Yi
Abstract: Developing highly active catalysts for the oxygen evolution reaction (OER) is of paramount importance for designing various renewable energy storage and conversion devices. Herein, we report the synthesis of a category of Co‐Pi analogue, namely cobalt‐based borate (Co‐Bi ) ultrathin nanosheets/graphene hybrid by a room‐temperature synthesis approach. Benefiting from the high surface active sites exposure yield, enhanced electron transfer capacity, and strong synergetic coupled effect, this Co‐Bi NS/G hybrid shows high catalytic activity with current density of 10 mA cm −2 at overpotential of 290 mV and Tafel slope of 53 mV dec −1 in alkaline medium. Moreover, Co‐Bi NS/G electrocatalysts also exhibit promising performance under neutral conditions, with a low onset potential of 235 mV and high current density of 14.4 mA cm −2 at 1.8 V, which is the best OER performance among well‐developed Co‐based OER electrocatalysts to date. Our finding paves a way to develop highly active OER electrocatalysts.